Kelet-Ausztria az új Közép-Európában – a jövőkép és az intézményrendszer kérdései - Fáth, János (Tér és Társadalom, 1997)
The essay deals with the efforts of the eastern provinces of Austria (Vienna, Upper Austria and Burgenland) to define their places, with special regard to the new geo- political conditions. One of the means for that, which mostly comes from research and political forums, is the creation of a prospect for the future. The author examines the prospects at three levels, i.e. province, East-Austrian region and interregional, beyond-border levels. The prospect projects the future situation of the region from the analysis of the inner forces and the environmental changes. From the future prospects we can derive the measures that need to be taken. On each level, institutions and conditions are needed which promote and allow the utilisation of the opportunities. The joint operation and joint decision making processes of the east Austrian provinces have only been accomplished in some partial fields. The future prospects of the provinces place special emphasis on wider regional connectíons reaching beyond the borders. The objective is to have in the future a Central European region which is not only a geographical but also an economic reality.